PETROGRAFI DAN PROSES DIAGENESIS BATUGAMPING FORMASI BATURAJA DI LINTASAN AIR SAKA, OKU SELATAN, SUMATERA SELATAN - sigit Maryanto (Pusat Survei Geologi, 2007)
The Early Miocene limestone of Baturaja Formation crops out along the Air Saka Section, having a measured thickness of 247 metres. This carbonate formation lies conformabty on the siliciclastic sediments of Talangakar Formation, and it is in turn, conformably overlain by the silicidastic sediments of Gumai Formation. The limestone was affected by several diagenetic processes, such as bioturbation, fossil cavity filling, replacement, cementation, recrystallization, micritization, dolomitization, authigenic-mineral formation, compaction, dissofution, stylolitization, and fracturing. Some of these diagenetic processes have a very weak to moderate coeficient of interrelationship. Keywords:Petrography, carbonate grains, cementation, meteoric, statistical test